Makna Konsep Akuntabilitas dan Transparansi dari Perspektif Al-Kindi - Armizha Rahmatika; isnalita isnalita (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2018)
Cases of bribery involving auditors and auditees become one form of fraud that is difficult to detect. This is because of both parties are equally enjoying the benefits of the outcome of such unethical and immoral behavior. The increasing number of corruption cases, specifically bribes in the government sector from year to year in Indonesia makes the role of public sector auditors such as BPK RI questioned. In addition, some of the perpetrators of corruption are adherents of Islam, which is interesting to criticize because Islam is a religion that upholds the value of honesty and truth. This research used qualitative research method with postmodernism paradigm because the researcher wanted to study the relevance of classical Islamic philosopher, Al-Kindi’s thought with the truth value in the accountability and transparency principle. It is done as an effort to integrate the meaning of accountability and transparency principle according to accounting with truth value according to Al-Kindi’s thought to get deeper meaning which if useful for auditor in carrying out its function, in order to work in accordance with professional ethic code by upholding ethics and morality value